Perkembangan Masyarakat Menuju Digitalisasi Di Kampung Tahu Binjai - Tiolina Evi; Olivia , Hastuti; Irwadi, Irwadi (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
The development of information and communication technology has encouraged global society in the era of digitalization, including in rural areas such as Kampung Tahu Binjai. However, these challenges in the form of limited access to technology, low digital literacy, and resistance to change are the main obstacles in this transformation process. This research aims to identify the problems faced by the people of Kampung Tahu Binjai in moving towards digitalization, recommend strategic approaches to accelerate adaptation, and spread the impact on social, economic and cultural aspects. The approach used includes participatory methods by conducting field observations, in-depth interviews, and digital literacy training based on local needs. The proposed solutions include providing technological infrastructure, integrated training programs, and strengthening collaboration with the private sector and government. The research results show that the implementation of digital initiatives such as e-commerce for marketing local tofu products and digital application-based education increases the economic welfare of the community by up to 35%. In addition, better digital literacy accelerates society's adaptation to new technologies, increases production efficiency and expands market access. In conclusion, digitalization has a significant impact in empowering the people of Kampung Tahu Binjai, as long as it is supported by an inclusive and sustainable strategy.